A multicenter prospective clinical cohort study of pulmonary cryptococcosis in adult non-HIV-infected patients in a southeastern province of China - Meiyan Chen; Shuyang Chen; Meng Wang; Huijuan Wang; Shengyuan Zeng; Liying Zhuang; Guoxiang Lai; Zongyang Yu; Yanjing You; Baosong Xie; Xiujuan Yao; Xiangqi Chen; et al. (Respiratory Research)
Abstract Background This study investigates the clinical presentations, diagnostic approaches, and treatment outcomes of pulmonary cryptococcosis (PC) in non-HIV patients in Fujian Province, and explores the correlation between immunological status and clinical features. Methods A prospective, multicenter cohort study was conducted from April 2017 to March 2022, involving 234 PC patients from 47 hospitals in nine prefecture-level cities in southeastern China’s Fujian Province. Results The study included 145 male and 89 female PC patients, average age 50.66 ± 14.11 years. Immunological status varied: 115 immunocompetent, 17 with potential immunodeficiency due to certain comorbidities, 69 with mild-to-moderate immunodeficiency, and 33 with severe immunodeficiency. Diabetes mellitus was the most common comorbidity. The prevalence of PC is higher in Eastern Fujian (51.7%). 18.4% of patients were exposed to birds/pigeons droppings prior to admission. 37.6% of patients were asymptomatic. Cough and expectoration were common symptoms. Radiologically, multiple lesions with subpleural and lower lobe involvement were typical. The Cryptococcus capsular antigen (CrAg) test showed a sensitivity of 94.9%. Fluconazole was the primary treatment (87.0%), followed by voriconazole. At final follow-up, 85.4% of patients had recovered or improved. Conclusions PC incidence in non-HIV-infected adults in Fujian is higher in males. Most patients were immunocompetent and from eastern Fujian, with few significant environmental exposures. Clinical and radiological findings were non-specific, highlighting diagnostic challenges. The CrAg test is a valuable diagnostic tool. Treatment with fluconazole and voriconazole resulted in favorable outcomes.